Selection of Most Suitable Candidates for the Talent Pool in a Furniture Manufacturing Company - Lenka Ližbetinová (University of Zagreb, Faculty of Forestry and Wood Technology, 2017)
This paper deals with the question of identification and development of talents in the company. The aim of the article is to find one of the possible solutions to increase the objectivity of identifying talents and finding valuable input data for planning effectively their further development. The objective is achieved by estimates of the weights of criteria and by the multicriteria decision making method. The proposed model for solving this problem is specific for companies in furniture industry, as well as for companies in other sectors. For this reason, the selected methods have been applied to a specific example of the Czech company operating in furniture industry for over twenty years.